Utilization of Video in Islamic Religious Education (IRE/PAI) Learning for Mentally Retarded Student at Public Special School (SLB-C) - Rozi, M. Asep Fathur; Ilawati, Lusi Nur; Mutadi, Mutadi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
This study aims to describe the implementation of PAI learning on developmentally disabled students at SLB C Negeri Tulungagung. The research method used is descriptive qualitative. This research results in PAI learning, which is carried out at SLB C Negeri Tulungagung by using the lecture, question and answer method, discussion, and a demonstration using video. The use of videos for developmentally disabled students is constructive in learning activities because they require repetition of material from the video. The supporting factors for PAI learning at SLB C Negeri Tulungagung are adequate facilities for learning at school, the participation of student guardians, quota assistance from the government, and the selection of appropriate learning media. While the inhibiting factors include the absence of special PAI teachers, the use of video learning media has not been maximized, not all parents of students have Android-based cell phones, so they are not optimal in delivering material.